2011
DOI: 10.1111/j.1460-2466.2011.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Language Brokering Frequency and Feelings on Mexican-Heritage Youth's Mental Health and Risky Behaviors

Abstract: Language brokering is the communication process where individuals with no formal training (often children of immigrant families) linguistically mediate for 2 or more parties (usually adult family members and individuals from mainstream culture). This study examined the direct and indirect effects of language brokering on mental health and risky behaviors. Mexican-heritage youth (N = 684) from schools in Phoenix, AZ, completed surveys at 3 waves from 7th through 8th grades. Language brokering frequency and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 51 publications
5
116
2
2
Order By: Relevance
“…Shifren concluded that the long-term effects of caring for parents and family members may not be ''universally negative and pervasive' ' (p. 190). Shifren's conclusions are also supported by other researchers (Gelman & Greer, 2011;Hooper, 2011;Kam, 2011;Vernig, 2011).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Shifren concluded that the long-term effects of caring for parents and family members may not be ''universally negative and pervasive' ' (p. 190). Shifren's conclusions are also supported by other researchers (Gelman & Greer, 2011;Hooper, 2011;Kam, 2011;Vernig, 2011).…”
supporting
confidence: 79%
“…Cultural factors that support filial responsibility seem to lessen the deleterious consequences of parentification (Hooper & Wallace, 2010;Kam, 2011;Telzer & Fuligni, 2009). Similarly, cultural factors, such as religious beliefs and practices, appear to function as protective factors reducing alcohol consumption among youth (Hill, Burdette, Weiss, & Chitwood, 2009;Walker, Ainette, Wills, & Mendoza, 2007).…”
Section: Moderating Effects Of Parentificationmentioning
confidence: 95%
“…The challenges of systematic observation have led to an overreliance on anecdotal evidence and retrospective reports (Cline et al 2010:118). Other scholars have collected survey data in schools, treating child brokers as an individual unit of analysis and relying on self-reported data (e.g., Kam 2011;Weisskirch and Alva 2002).…”
Section: Methodological and Theoretical Dimensions Of Child Brokeringmentioning
confidence: 99%
“…"Parentification" is common among children whose parents have addictions or serious illnesses; these role reversals carry wide-ranging risks for young people (e.g., Byng-Hall 2008;Kam 2011). Parentification can occur in immigrant families, but these children are more often desirous of their parents' retained authority, which can also augment their brokering efforts (Katz 2014;Orellana 2009).…”
Section: Bringing In the Familymentioning
confidence: 98%
“…Fortunately, the outcomes of language and cultural brokering are not universally negative for these youth. Brokering frequency leaves children little free time to engage in risky behavior, and positive feelings about their brokering may help reduce their risky behaviors (Kam 2011).…”
Section: Practices Of Cultural Communication Competencementioning
confidence: 99%